2017
DOI: 10.1007/s10974-017-9476-6
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II sequences for Lethocerus indicus

Abstract: We present the genomic and expressed myosin II sequences from the giant waterbug, Lethocerus indicus. The intron rich gene appears relatively ancient and contains six regions of mutually exclusive exons that are alternatively spliced. Alternatively spliced regions may be involved in the asymmetric myosin dimer structure known as the interacting heads motif, as well as stabilizing the interacting heads motif within the thick filament. A lack of negative charge in the myosin S2 domain may explain why Lethocerus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This also correlates with the increased ATPase rate for the IFM isoform (40). We conclude that the IHM is present in both isoforms of insect myosin II but is less stable in the flight muscle, presumably as a result of differences in critical regions of the protein that are encoded by alternative exons (40,103). This is consistent with the lower level of charge attraction predicted (on the basis of sequence comparison) in the IHM interfaces of IFM compared with EMB myosin (70,103).…”
Section: Discussionsupporting
confidence: 79%
“…This also correlates with the increased ATPase rate for the IFM isoform (40). We conclude that the IHM is present in both isoforms of insect myosin II but is less stable in the flight muscle, presumably as a result of differences in critical regions of the protein that are encoded by alternative exons (40,103). This is consistent with the lower level of charge attraction predicted (on the basis of sequence comparison) in the IHM interfaces of IFM compared with EMB myosin (70,103).…”
Section: Discussionsupporting
confidence: 79%
“…This is probably a consequence of the intrinsic flexibility of the IHM paired heads arrangement (Yang et al 2015a) especially of the free swaying heads as explained below (Brito et al 2011;Sulbarán et al 2013). Interestingly, it has been recently reported that a lack of negative charge in S2 may explain why Lethocerus thick filaments display an IHM perpendicular to the filament axis, rather than a parallel one as seen in tarantula (Fee et al 2017). In retrospect, both head densities resolved in frozenhydrated 3D reconstructions (Fig.…”
Section: Solving the Ihm Near Atomic And The Hmm Atomic Structuresmentioning
confidence: 79%
“…1D), which does not fold back to contact its own S2 (Hu et al, 2016); and thus the S2-blocked head contact must not be strictly required to form a stable IHM. Moreover, the Lethocerus flight muscle myosin sequence lacks the net negative charge (Fee et al, 2017), which is thought to stabilize the folded-back S2-blocked head contact (Alamo et al, 2016; Blankenfeldt et al, 2006). We conclude that while the blocked head-S2 interaction provides stability in some myosin species, it is not essential to formation of the IHM in all cases.…”
Section: Discussionmentioning
confidence: 99%